Kaposiform hemangioendothelioma in an unusual site: A report of two cases in children - Sumanta Bhattacharya; Paromita Roy; Uttara Chatterjee; Arpita Bhattacharyya (Wolters Kluwer Medknow Publications, 2022)
Kaposiform hemangioendothelioma (KHE) is a locally aggressive vascular tumor usually seen in children. It is frequently associated with Kasabach-Merritt phenomenon. Here we report two cases of KHE: the first case being an 11-month-old boy who came with massive swelling on the face and violaceous discoloration. The second case was a 7-year-old boy who presented with respiratory distress and bleeding manifestations. CT scan chest showed a large mass involving the anterior mediastinum. Histologic examination of resected masses from both these cases showed features of KHE involving subcutaneous tissue and thymus, respectively. Although cutaneous and subcutaneous location is common, thymic involvement is unusual. It is important to distinguish KHE from infantile haemangioma, tufted angioma, spindle-cell haemangioma, verrucous malformation and Kaposi sarcoma. Histologic features, supportive immunohistochemistry and the clinical profile together are helpful to differentiate KHE from other vascular lesions.